Biodiversity And Phylogenetic Studies Of Land Snails (Pulmonata: Stylommatophora) In Peninsular Malaysia - Bakar, Siti Balkhis Abu (2013)
A total of 24 species from 21 genera in 14 families sampled from 19 locations in Peninsular Malaysia were identified by looking at their shell morphological characteristics and compared with voucher specimens in Natural History Museum, London. All the specimens were successfully sequenced based on the double amplification of rRNA genes that comprised of the conserved and variable regions (5.8S gene, the complete ITS-2 region and the large subunit 28S gene). These Malaysian taxa sequences were then analyzed together with available 179 Stylommatophoran data based on 844 bp sequences to investigate their phylogenetic relationships. Both Neighbour-Joining (NJ) and Maximum Likelihood (ML) phylogenetic trees remained monophyletically, supported (as in previous analysis) with the splitting into ‘achatinoid’ and ‘non-achatinoid’ clades (40% and 100% in NJ and ML bootstrap values, respectively) with the Malaysian inclusion. The ‘achatinoid’ clade had four distinct and stable clusters’ namely (1) Plectopylidae, (2) Streptaxidae and Diapheridae (Streptaxoidea), (3) Ferussaciidae, and (4) a lineage that includes Subulinidae, Achatinidae, Coeliaxidae and Thyrophorellidae. From the seven major groups in the ‘non-achatinoid’ clade, the taxonomic status of Helicoidea, Orthalicoidea, Elasmognatha and Orthurethra remained unresolved as no additional or only a single representative taxon was obtained in the present study. However, groups within the Limacoidea, Clausilioidea and Arionoidea taxa require further investigations that may lead to taxonomic revisions.